2017
DOI: 10.3844/ajidsp.2017.3.12
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HSV1 and HSV2 among HIV Patients in Northern South Africa as Determined by Real Time PCR in Urine Samples

Abstract: The present study determined the prevalence of HSV-1 and 2 among HIV patients in Northern South Africa and identified potential risk factors. Urine samples were collected from patients attending different HIV clinics in Limpopo Province. Total genomic DNA was isolated from these samples using GenElute Blood Genomic DNA Kit and real time PCR protocols were used for the detection of HSV1 and HSV2. Demographic, clinical and socioeconomic data were collected using a structured questionnaire. The overall prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…In sub-Saharan Africa, a moderate number of studies 1719 have reported a high HSV-2 seroprevalence among WLHIV, with an estimated 93.3% prevalence reported in KwaZulu-Natal, South Africa 19 where this study was conducted. We found two studies in South Africa that performed diagnostic testing to determine active HSV-2 infection prevalence of 10.8% in WLHIV 10 and 13.7% 9 in PLHIV. However, few studies have determined the incidence and predictors of HSV-2 PCR positivity among PLHIV in sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In sub-Saharan Africa, a moderate number of studies 1719 have reported a high HSV-2 seroprevalence among WLHIV, with an estimated 93.3% prevalence reported in KwaZulu-Natal, South Africa 19 where this study was conducted. We found two studies in South Africa that performed diagnostic testing to determine active HSV-2 infection prevalence of 10.8% in WLHIV 10 and 13.7% 9 in PLHIV. However, few studies have determined the incidence and predictors of HSV-2 PCR positivity among PLHIV in sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 99%
“…In South Africa, a global hotspot of the HIV epidemic, 8 two studies have estimated 13.7% prevalence of HSV-2 in men and women living with HIV 9 and 10.8% prevalence in WLHIV. 10 In WLHIV, HSV-2 coinfection with HIV causes increased morbidity through prolonged genital herpes recurrences, especially among patients with lower immune status. 3 This makes their HIV care more burdensome due to more clinic visits and treatments, often leading to poorer clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%